Percieved Brand Quality in Uganda’s Pharmaceutical Industry: The Role of Country of Origin, Marketing Orientation and Brand Affordability - Ngoma, Muhammed; Ntale, Peter Dithan (Advances in Management and Applied Economics, 2015)
The study set out to determine the role played by country of origin, marketing orientation and brand affordability in influencing the perceived brand quality of pharmaceuticals in Uganda. In a sample of 352 doctors selected through a stratified random sampling, statistical analysis revealed significant positive relationships between the variables, that is; Country of Origin, pharmaceutical marketing orientation, brand affordability and perceived brand quality. Regression results confirmed that country of origin image, brand affordability and marketing orientation were strong predictors of perceived brand quality. Overall, the independent variables explained 32.4 % of the variance in perceived brand quality. It is therefore suggested that the pharmaceutical companies should analyze the country of origin image in detail and recognize the capacity of the country within different product categories. However, given the continuous globalization of markets, it is possible to neutralize the effect of country-of-origin on the evaluation of product quality and the influence on purchasing decisions. Evidence from the literature revealed that if other forms of product quality attributes were highlighted during the product’s promotion and marketing campaigns, country-of-origin would have low effect on consumers’ perception of product quality in the pharmaceuticals.
Keywords: Country of Origin; Pharmaceutical Marketing Orientation; Brand affordability